Factors influencing generation Z’s purchase intention of second-hand clothing in Malaysia - Kho, Wen Yi; Ng, Ting Xuan (2023)
The fashion sector has a significant environmental effect which has encouraged second-hand clothing to be a solution to reduce the impact. As a result, thrifting has slowly become a trend worldwide, especially with Generation Z. As Generation Z is starting to be more conscious of sustainability issues, the chances of them purchasing second-hand clothing is higher. However, many factors can influence their motivation to purchase second-hand clothing. Therefore, this study examines the factors influencing Generation Z's purchase intention towards second-hand clothing in Malaysia. The theoretical framework of this study, the Theory of Planned Behaviour, is used to investigate the intention to perform a certain behaviour, which includes 3 independent variables, which are attitude (ATT), social influence (SI), and perceived behavioural control (PBC). This study also considers environmental and economic values as two additional independent variables influencing the purchase intention towards second-hand clothing. A questionnaire is employed in this study to obtain data from 385 respondents. Statistical Package for the Social Sciences (SPSS) software is then used to analyse the data obtained. This study performed a reliability test, Pearson's correlation coefficient analysis, and multiple regression analysis to demonstrate the relationship between the independent and dependent variables. The results of this study show that 3 independent variables, which are attitude, social influence, and economic value, significantly influence the dependent variable. However, perceived behavioural control and environmental value do not significantly influence the dependent variable. This study's findings can help researchers understand the variables influencing Generation Z's purchase intention for second-hand clothing in Malaysia, and practitioners design effective strategies to market second-hand clothing and increase its attraction to the younger generation.